Risk Mitigation of PGA Surgical Suture Distribution in Distribution Companies - Alfonsia Febriyana; Hermanto Siregar; Arif Imam Suroso (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: The demand for PGA surgical suture is increasing, which was recorded from 2017-2019, reaching 148 million in the world and 1.2 million in Indonesia. This is in line with the increase in surgery. Currently, many foreign medical device products are supplied from imports, reaching 70%, and have high prices. PT XYZ is one of the medical device distributor companies that collaborates with companies in the European region as suppliers. The company often experiences problems in procuring product inventory because it depends on one supplier, which affects supply chain performance and creates various risks in its business processes.Purpose: This research focused on risk mitigation at PT XYZ.Design/methodology/approach: The HOR analysis and fishbone method.Findings/Result: Based on the HOR analysis and fishbone method, 3 priority sources of risk that must be mitigated are supplier errors, fluctuating demand, and limited storage space. Furthermore, the mitigation that must be done is to encourage suppliers to build factories in Indonesia, provide quarterly order forecasting, and hold regular meetings for evaluation and strategy making. Keywords: fishbone, house of risk, PGA surgical suture, risk, risk mitigation